Robots serve humans in public places—KeJia robot as a shopping assistant. (18th May 2017) - Chen, Yingfeng; Wu, Feng; Shuai, Wei; Chen, Xiaoping
This paper reports the project of a shopping mall service robot, named KeJia, which is designed for customer guidance, providing information and entertainments in a real shopping mall environment. The background, motivations, and requirements of this project are analyzed and presented, which guide the development of the robot system. To develop the robot system, new techniques and improvements of existing methods for mapping, localization, and navigation are proposed to address the challenge of robot motion in a very large, complex, and crowded environment. Moreover, a novel multimodal interaction mechanism is designed by which customers can conveniently interact with the robot either in speech or via a mobile application. The KeJia robot was deployed in a large modern shopping mall with the size of 30, 000 m 2 and more than 160 shops; field trials were conducted for 40 days where about 530 customers were served. The results of both simulated experiments and field tests confirm the feasibility, stability, and safety of the robot system.